The emergence of anthroponotic cutaneous leishmaniasis following the earthquake in southern villages of bam district, southeastern iran, 2010. - Mohammad Reza Aflatoonian; Iraj Sharifi; Somayeh Poursmaelian; Maryam Hakimi-Parizi; Nasser Ziaali (Tehran University of Medical Sciences, 2013)
Background: The objective of this study was to assess the epidemiological characteristics of a new emerging focus of cutaneous leishmaniasis (CL) in southern villages of Bam District, southeastern Iran, 2010. Methods: A house-to- house census survey of 5544 individuals were interviewed and physically examined for the presence of active lesions or scars. Diagnosis was confirmed by direct smears, cultures and identification by PCR. The data were entered into a computer and SPSS ver. 15. Results: Overall, 1.2% of the inhabitants were infected, 0.5% active and 0.7% scars and females were more signifi- cantly infected (1.7%) than males (0.8%), (P= 0.003). All age groups were equally affected. Most of the lesions were on the face and majority had single lesion. Most of the cases appeared from 2006 to 2008 during the CL epidemic in the city of Bam. PCR indicated L. tropica as the causative agent. Conclusion: The presence of non-immune individuals along with suitable ecological conditions could induce a new emerging focus of ACL in villages.